Hubungan Refleks Primitif dengan Kemampuan Motorik Kasar pada Anak Tunadaksa di SLBN Kota Jambi - Wanti Hasmar; Faridah Faridah (Science: Indonesian Journal of Science, 2026)
Reflexes are motor patterns that develop in utero and after birth, aimed at survival and developmental needs while the brain is developing. Reflexes are activated through sensors (touch and proprioception) during typical development; these automatic movement patterns will be integrated as controlled movements. Reflex movements are the first foundation of the nervous system. If the foundation of primitive reflexes and postural reflexes is unstable, weak, or there is a gap in its development, it will weaken all other levels to some extent. Motor, perception, speech, and conceptualization will also be unstable, and damage to one or all of these areas can occur, thus causing higher-level functional areas to be affected. This study aims to determine the relationship between gross motor skills of children with spastic CP and primitive reflexes. With a cross-sectional design, this study is a correlational study. The sampling technique used is total sampling. The population in this study were children with spastic CP. The study sample consisted of 14 children who met the inclusion and exclusion criteria. Gross motor skills were assessed using the Gross Motor Function Measure (GMFM) scale and primitive reflexes using the primitive reflex value scale. The results of the study showed a significant relationship between 10 primitive reflexes and gross motor skills in children with physical disabilities (Spastic CP) such as ATNR (ρ = 0.002), STNR (ρ = 0.012), Moro (ρ = 0.003), Graps (ρ = 0.002), Spinal galant (ρ = 0.002), Optical Righting (ρ = 0.002), Head Righting (ρ = 0.021), Head righting acting to body (ρ = 0.003), Body Righting (ρ = 0.003), Body righting acting to body (ρ = 0.003).